Pengaruh Moderasi Konsensus Strategis Terhadap Hubungan Antara Lean Manufacturing dengan Mekanisme Pengendalian Manajemen - Hermanto Tupamahu, Kevin; dewi, syahrina (Universitas Muhammadiyah Surakarta, 2023)
The purpose of this study was to investigate and examine the contingency models for discussed the moderating effect of strategic consensus to the relationship between lean manufacturing with management control mechanisms used by the companies. The sample of this study is a manufacturing firms in Java Indonesia, represented by a director or managers. The sampling method uses a purposive sampling method. Data collection techniques in this study used survey questionnaire. The number of research samples successfully collected and can be used are 104 firms. In this study, hypothesis testing is carried out using Structural Equation Modeling (SEM) with use the application program AMOS 24. The research findings show that strategic consensus as a moderating variable has been proven to strengthen the relationship between lean management strategies and management control mechanisms.